2021
DOI: 10.4049/jimmunol.2001188
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Activation Gene-3 Regulates Dendritic Cell Metabolic Programing and T Cell Priming Function

Abstract: Deficiency of lymphocyte activation gene-3 (LAG3) is significantly associated with increased cardiovascular disease risk with in vitro results demonstrating increased TNF-α and decreased IL-10 secretion from LAG3-deficient human B lymphoblasts. The hypothesis tested in this study was that Lag3 deficiency in dendritic cells (DCs) would significantly affect cytokine expression, alter cellular metabolism, and prime naive T cells to greater effector differentiation. Experimental approaches used included differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…We have also recently reported that bone marrow–derived dendritic cells lacking LAG3 showed enhanced antigen-induced CD4 + T cell activation and proliferation, strongly suggesting that LAG3 in non–T cells significantly influences T cell function. 27 …”
Section: Discussionmentioning
confidence: 99%
“…We have also recently reported that bone marrow–derived dendritic cells lacking LAG3 showed enhanced antigen-induced CD4 + T cell activation and proliferation, strongly suggesting that LAG3 in non–T cells significantly influences T cell function. 27 …”
Section: Discussionmentioning
confidence: 99%
“…LAG-3 is also involved in DC immune suppression. LAG-3 deficiency has led to increased TNFα secretion and upregulation of glycolysis in murine bone marrow derived DC ( 111 ).…”
Section: Overcoming Strategies To Tackle DC Impairments In the Tmementioning
confidence: 99%
“…Initial analyses of LAG3 expression in dendritic cell (DC) subsets showed high LAG3 expression by plasmacytoid but not lymphoid or myeloid conventional DCs 7 . However, a more recent study demonstrated a role for LAG3 on bone marrow derived DCs in optimal T cell priming 51 . Due to these controversies, the impact of LAG3 deficiency in recipient APCs needs to be carefully dissected in future studies.…”
Section: Discussionmentioning
confidence: 99%